Tyrosine 601 of Bacillus subtilis DnaK Undergoes Phosphorylation and Is Crucial for Chaperone Activity and Heat Shock Survival‡ - Shi, Lei; Ravikumar, Vaishnavi; Derouiche, Abderahmane; Macek, Boris; Mijakovic, Ivan (Frontiers in Microbiology, 2016)
In order to screen for cellular substrates of the Bacillus subtilis BY-kinase PtkA, and its cognate phosphotyrosine-protein phosphatase PtpZ, we performed a triple SILAC-based quantitative phosphoproteome analysis. Detected tyrosine phosphorylation sites for which the phosphorylation level decreased in the ΔptkA strain and increased in the ΔptpZ strain, compared to the wild type, were considered as potential substrates of PtkA/PtpZ. One of those sites was the residue tyrosine 601 of the molecular chaperone DnaK. We confirmed that DnaK is a substrate of PtkA and PtpZ by in vitro phosphorylation and dephosphorylation assays. In vitro, DnaK Y601F mutant exhibited impaired interaction with its co-chaperones DnaJ and GrpE, along with diminished capacity to hydrolyze ATP and assist the re-folding of denatured proteins. In vivo, loss of DnaK phosphorylation in the mutant strain dnaK Y601F, or in the strain overexpressing the phosphatase PtpZ, led to diminished survival upon heat shock, consistent with the in vitro results. The decreased survival of the mutant dnaK Y601F at an elevated temperature could be rescued by complementing with the wild type dnaK allele expressed ectopically. We concluded that the residue tyrosine 601 of DnaK can be phosphorylated and dephosphorylated by PtkA and PtpZ, respectively. Furthermore, Y601 is important for DnaK chaperone activity and heat shock survival of B. subtilis.